Effect of tocilizumab on neutrophils in adult patients with rheumatoid arthritis: pooled analysis of data from phase 3 and 4 clinical trials. (18th December 2016) - Moots, Robert J.; Sebba, Anthony; Rigby, William; Ostor, Andrew; Porter-Brown, Benjamin; Donaldson, Francis; Dimonaco, Sophie; Rubbert-Roth, Andrea; van Vollenhoven, Ronald; Genovese, Mark C.
Abstract: Objectives. To investigate changes in neutrophil count and occurrences of infection in RA patients treated with the IL-6 receptor-α inhibitor tocilizumab (TCZ). Methods. Data were pooled from patients who received i.v. TCZ (4 mg/kg + MTX, 8 mg/kg ± DMARDs, 10 mg/kg) or placebo + DMARDs in phase 3/4 clinical trials, long-term extensions or a pharmacology study. Neutrophil counts were measured routinely according to the Common Toxicity Criteria for Adverse Events grades; TCZ dosing was adjusted if necessary. Covariates associated with decreased neutrophil counts were assessed with multivariate regression analysis. Infection rates within 30 days of neutrophil count changes were calculated per 100 patient-years of TCZ exposure. Results. In placebo-controlled parts of trials, more TCZ-treated than placebo-treated patients had grade 1/2 or 3/4 neutrophil counts (TCZ: 28.2%/3.1%; placebo: 8.9%/0.2%). In placebo-controlled trials + long-term extensions, 4171 patients provided 16204.8 patient-years of TCZ exposure. Neutrophil counts decreased through week 6 from baseline [mean (s .d .) change, –2.17 (2.16) × 10 9 /l) and remained stable thereafter. Rates (95% CI) of serious infections within 30 days of normal [4.66 (4.31, 5.03)], grade 1/2 [2.48 (1.79, 3.34)] and 3/4 [2.77 (0.34, 10.01)] neutrophil counts were similar. Baseline neutrophil count <2 × 10 9 /l and female gender were associated with grade 3/4 neutrophil counts [odds ratio (OR) (95% CI): 19.02 (6.76, 53.52), 2.55 (1.40, 4.66)]. Patients who stopped TCZ in response to decreased neutrophil count returned more quickly to normal levels than patients who reduced or continued their dose. Conclusion. Decreases in neutrophil counts in patients taking TCZ do not appear to be associated with serious infections and are normalized by current risk mitigation guidelines.